Perancangan Mesin Organic Bin Recycler dengan Bioaktivator untuk Menghasilkan Pupuk Kompos - Zamri, Aidil (Jurnal Ilmiah Poli Rekayasa, 2023)
The Organic Bin Recycler machine is designed on a small scale to be placed in the kitchen and functions as a special trash can for organic waste. The design of this machine aims to reduce the problems related to the disposal of organic food waste and kitchen waste, reduce environmental pollution, and to produce compost. Composting in this machine is done by adding a bioactivator. The design is carried out with the catia v5 software in accordance with the calculations that have been done. The machine has two main components, the organic waste crusher, and the waste stirring component. The crusher uses an electric motor with a power of 0.75 kW or 1 Hp with a rotation of 1400 rpm. The stirring component uses a motor with a power of 0.18 kW or 0.245 Hp and a rotation of 1400 rpm which is reduced to 30 rpm using a 1:20 reducer gearbox. The transmission system used is a belt and pulley transmission.